INCREASING NITROGEN EFFICIENCY WITH MODIFIED UREA-HUMIC ACID- BIOCHAR (UAB) AND THEIR EFFECTS ON THE GROWTH OF CORN. - Rahmi, Eka Rahmi; Mariana, Mariana Mariana; Muliana, Muliana Muliana (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2025)
Nitrogen is the element most needed by plants but has a low utilization efficiency by plants. The problem of low fertilizer efficiency can be overcome by controlling the solubility of the fertilizer, so that nutrients can be released slowly. The purpose of this research is to modify the physical mixture of urea fertilizer by using biochar and humic acid (UBA) so as to reduce the solubility of Nitrogen. Then study the nitrogen release pattern (ammonium and nitrate) of UBA. Another objective was to study the uptake of N nutrients from UBA fertilizer on corn plant growth. This research consists of several stages, namely the modification stage of the urea mixture with biochar and humic acid. Incubation of soil for 12 weeks, then application of UBA fertilizer on corn plants. The results showed that the release pattern of ammonium ions decreased by 28% with increasing incubation time. U3 and U4 treatments using Polyvinyl Alcohol (PVA) coatings were able to reduce the release of total nitrogen in the form of N-ammonium (N-NH4+) and N-nitrate (N-NO3-) and release it more slowly to become still available until the end of the incubation period compared to the urea control. Maize plant height growth due to the application of UBA fertilizer without coating gave a positive effect on the growth of plant height and leaf width. The highest growth and best leaf width were shown by UBA U2 fertilizer treatment (5% humate without filer/coating). The UBA fertilizer formulation using PVA coating is less suitable for the N needs of corn plants because the amount of N released by the fertilizer does not match the amount of N needed by corn plants during their growth period.